Genetic and biochemical analysis of the Hel308 Helicase in the Archaeon Haloferax volcanii - Lever, Rebecca (2020)
Hel308 is a monomeric 3’ to 5’ DNA helicase conserved throughout archaea and metazoans, but is absent from bacteria and fungi. Hel308 acts analogously to RecQ-family helicases, which serve as guardians of genome stability. Hel308 has been implicated in a variety of overlapping DNA repair pathways, including homologous recombination. However, the exact role of Hel308 remains elusive. Haloferax volcanii was used as a model archaeon to study cellular role of Hel308.